Investigation of the Air Pollution Event in Beijing-Tianjin-Hebei Region in December 2016 Using WRF-Chem - Dongdong Wang; Baolin Jiang; Fangzhou Li; Wenshi Lin (Advances in Meteorology)
The online coupled weather research and forecasting model with chemistry (WRF-Chem) was used to investigate an air pollution event during December 2016 in Beijing-Tianjin-Hebei urban agglomeration. Evaluation indicates that WRF-Chem captured the main weather conditions and pollutant distribution in this event. The primary meteorological drivers of air pollution formation were stationary atmospheric flows in both vertical and horizontal directions. High relative humidity and a strong temperature inversion accelerated event formation. In the shallow temperature inversion layer, aerosol particles were strongly confined near the surface, producing high surface contaminant concentrations. In addition, based on a normal experiment, three sensitivity experiments were constructed by adding hypothetical terrain (HT) of 400, 300, and 200 meters, over the region 115°E, 38.8°N to 117.54°E, 38.8°N. The results indicate that pollutants were diffused and transported below 400 meters, and the pollutant amounts concentrated south of the HT because of the HT blocking effect. Nevertheless, because there were less total contaminants north of the HT in the normal run, there was a slight decrease in pollutants north of the HT. There were some increases in pollution north of the HT because of local emissions, which were obstructed by the HT. The higher the HT, the stronger the blocking effect.